Removal of heavy metal ions by modified sawdust of walnut - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2003)
Modified walnut sawdust was found to be effective in removing Ni(II), Cd(II) and Pb(II) from aqueous solution. The extent of removal depends on the contact time, concentration and temperature of the solution. The equilibrium time was found to be about 60 min. The adsorption rate constants were calculated by kinetics which fit a pseudo first-order and second-order laws. Experiments were carried out at three different temperatures, expressed as both Freundlich and Langmuir isotherms, and Freundlich and Langmuir constants as well as the thermodynamic parameters DeltaG, DeltaH and DeltaS were calculated. A possible explanation for the adsorption of metal ions by the sawdust may be attributed to the exchange between metal ions and acidic protons in sawdust matter.
Keywords: adsorption; heavy metals; removal; sawdust; kinetics; thermodynamics; AQUEOUS-SOLUTIONS; ADSORPTION THERMODYNAMICS; MODIFIED BARKS; KINETICS; COPPER; CARBOFURAN